Romania's National Recovery and Resilience Plan – a Set of Reforms and Investments for the Increase of the Nominal and Real Convergence - Iulian Nicolae Vasiloiu (Ovidius University Annals: Economic Sciences Series, 2022)
The 2020 pandemic has led to economic recession in the European Union, rising unemployment, falling purchasing power among the majority of citizens and has forced national institutions to intervene with many measures that have led to rising budget deficits and public debt. As of 2021, the Recovery and Resilience Facility has been approved at EU level, to the purpose of economic recovery and increasing the economic resilience of EU Member States. This paper analyses Romania's fulfilment of the nominal convergence criteria, the evolution of Romania's gross domestic product pre- and post-pandemic, the main measures foreseen in Romania's National Recovery and Resilience Plan to ensure a green, digital transition and economic and social resilience, as well as the funds available to Romania through the NRRP for investments and structural reforms necessary for economic growth and nominal convergence.